Incidence and management of choledocholithiasis on routine intraoperative cholangiogram: a 5‐year tertiary centre experience. Issue 1 (22nd December 2022) - Ng, Justin; Teng, Roy; Izwan, Sara; Chan, Erick; Kumar, Maarisha; Damodaran Prabha, Ramesh; Puhalla, Harald
Abstract: Background: The incidence of choledocholithiasis on routine intraoperative cholangiogram (IOC) during cholecystectomy is approximately 12%. Cholecystectomy without IOC may lead to undiagnosed choledocholithiasis placing patients at risk of complications such as pancreatitis or cholangitis. This study aims to determine the incidence of choledocholithiasis intraoperatively as well as the associated risk factors and the methods of management. Methods: A retrospective observational analysis of all laparoscopic cholecystectomies with IOC at the Gold Coast Hospital and Health Service from 1 January 2016 to 2 December 2021 was carried out. Patient demographics, operative data and cholangiogram findings were collected from electronic medical systems. Results: A total of 3904 cholecystectomies were carried out over the study period. 3520 (90.1%) had an IOC, and 474 (13.4%) had positive IOC findings. 158 (33.3%) of the cases were managed intraoperatively with hyoscine butylbromide with or without intravenous glucagon followed by biliary tree flushing alone, 183 (38.6%) received transcystic bile duct exploration (TCBDE) with a success rate of 83% and 167 (35.2%) received endoscopic retrograde cholangiopancreatography (ERCP). Choledocholithiasis was incidental in 44 (9.28%) patients. Conclusion: Incidental choledocholithiasis during routine IOC is not uncommon. Management predominantly includes intraoperative TCBDE or postoperatively via an ERCP. This study has not found reliable preoperative factors to predict choledocholithiasis based on preoperative clinical, radiological and biochemical factors. A small proportion of patients received preoperative endoscopic intervention, and the decision‐making process requires further investigation. Abstract : The incidence of choledocholithiasis on routine intraoperative cholangiogram (IOC) during cholecystectomy is approximately 12%. This study evaluates the management and risk factors of choledocholithiasis across 3904 cases of cholecystectomies over 5 years at a major tertiary hospital. Choledocholithiasis is not uncommon and our data shows approximate equal distribution of cases requiring transcystic bile duct exploration, endoscopic retrograde cholangiopancreatography and intraoperative hyoscine butylbromide, glucagon and biliary tree flushing.